Milk composition and lactation of beta-casein-deficient mice. - Kumar, S (1994)
beta-Casein is a major protein component of milk and, in conjunction with the other caseins, it is assembled into micelles. The casein micelles determine many of the physical characteristics of milk, which are important for stability during storage and for milk-processing properties. There is evidence that suggests that beta-casein may also possess other, nonnutritional functions. To address the function of beta-casein, the mouse beta-casein gene was disrupted by gene targeting in embryonic stem cells. Homozygous beta-casein mutant mice are viable and fertile; females can lactate and successfully rear young. beta-Casein was expressed at a reduced level in heterozygotes and was completely absent from the milk of homozygous mutant mice. Despite the deficiency of beta-casein, casein micelles were assembled in heterozygous and homozygous mutants, albeit with reduced diameters. The absence of beta-casein expression was reflected in a reduced total protein concentration in milk, although this was partially compensated for by an increased concentration of other proteins. The growth of pups feeding on the milk of homozygous mutants was reduced relative to those feeding on the milk of wild-type mice. Various genetic manipulations of caseins have been proposed for the qualitative improvement of cow's milk composition. The results presented here demonstrate that beta-casein has no essential function and that the casein micelle is remarkably tolerant of changes in composition.